2010
DOI: 10.1016/j.febslet.2010.08.050
|View full text |Cite
|
Sign up to set email alerts
|

MEGF10 functions as a receptor for the uptake of amyloid‐β

Abstract: Edited by Jesus AvilaKeywords: MEGF10 Amyloid-b Endocytosis Lipid raft pathway Alzheimer's disease a b s t r a c t MEGF10 is predominantly expressed in the brain and known to function as a phagocytic receptor. Here, we provide evidence that MEGF10 is involved in the uptake of amyloid-b peptide (Ab42) in the brain. Overexpression of MEGF10 dramatically increased Ab42 uptake in Hela cells. Knockdown of endogenous MEGF10 expression significantly decreased Ab42 uptake in N2A neuroblastoma cells. MEGF10-mediated Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…Nevertheless, little is known about the CTXN3 protein (described for the first time in 2007): it has a single membrane-spanning domain and appears to be expressed only in the kidney and in the brain. 46 Another interesting gene of this locus, MEGF10, encodes a phagocytic receptor that could have a role in Aβ 1–42 uptake in the brain 47 and a suggestive association with cognitive decline in AD patients has been recently reported within this gene. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, little is known about the CTXN3 protein (described for the first time in 2007): it has a single membrane-spanning domain and appears to be expressed only in the kidney and in the brain. 46 Another interesting gene of this locus, MEGF10, encodes a phagocytic receptor that could have a role in Aβ 1–42 uptake in the brain 47 and a suggestive association with cognitive decline in AD patients has been recently reported within this gene. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduction of cellular cholesterol and sphingolipid levels decrease Ab uptake [114]. More directly, treatment of lipid raft-dependent endocytosis inhibitor or inhibition of clathrin-dependent endocytosis decreases Ab uptake [47,115,116]. Collectively, such direct interaction with lipid rafts and clathrinmediated endocytosis may provide way(s) for Ab uptake.…”
Section: Receptors For Ab Internalizationmentioning
confidence: 99%
“…The authors further showed that reduction of cellular cholesterol and sphingolipid levels significantly decreased A β uptake [65]. A recent study by Singh et al [66] using mouse neuroblastomas also found colocalization of internalized A β with CTxB. The authors pharmacologically inhibited lipid raft-dependent endocytosis which resulted in decreased uptake of soluble A β [66].…”
Section: Aβ Binding Aggregation and Internalization At Lipid Raftsmentioning
confidence: 99%
“…A recent study by Singh et al [66] using mouse neuroblastomas also found colocalization of internalized A β with CTxB. The authors pharmacologically inhibited lipid raft-dependent endocytosis which resulted in decreased uptake of soluble A β [66]. Thus far it is unclear whether the lipid components or the associated receptor proteins are responsible for initiating A β uptake at lipid rafts.…”
Section: Aβ Binding Aggregation and Internalization At Lipid Raftsmentioning
confidence: 99%